The effect of single nucleotide polymorphism on susceptibility of osteoarthritis: recent progression and implications - Chen, Wenxiang; Wang, Yiying; Zhao, Jianning; Bao, Nirong (Annals of Joint; Vol 2 (August 2017): Annals of Joint, 2017)
Osteoarthritis (OA) is a disabling and malformation disease that affects multiple joints, especially hip and knee joint, which is characterized by degeneration and progressive loss of articular cartilage with pathological changes in bone, synovium, and soft tissues of affected joints. Polymorphisms in several genes, such as TIMP3, interleukin-6 (IL-6), IL-16, CDH2, HIF1A, and WISP1, have been demonstrated to be protective factors of OA. However, polymorphisms in other genes including ADAM12, DVWA and ACE were considered to be correlated with increased risk of OA. The present review focuses on the association between single nucleotide polymorphisms (SNPs) locus and susceptibility of OA.